2010
DOI: 10.1177/0013124510370946
|View full text |Cite
|
Sign up to set email alerts
|

Low Birth Weight, Preschool Education, and School Remediation

Abstract: Studies have documented a strong relationship between low birth weight status and adverse child outcomes such as poor school performance and need for special education services. Following a cohort of over 1,300 low-income and predominately African American children in the Chicago Longitudinal Study we investigated whether birth weight and family socio-economic risk measured at the time of the child’s birth predicts placement into special education classes or grade retention in elementary school. Contrary to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 41 publications
(53 reference statements)
0
5
0
Order By: Relevance
“…(p. 10) Similarly, based on their study of 1,364 racially diverse public school children, Dupere, Leventhal, Crosnoe, and Dion (2010) concluded that the reading score discrepancy between low-income and wealthier students could be explained largely by the institutions to which they had access since birth. For example, poor and working class families rarely have access to high-quality early childhood education programs-the kind that support children's language (and other) learning in intensive, engaging ways (Kilburn & Karoly, 2008;Temple, Reynolds, & Arteaga, 2010).…”
Section: Stereotype 4: Poor People Are Linguistically Deficientmentioning
confidence: 99%
“…(p. 10) Similarly, based on their study of 1,364 racially diverse public school children, Dupere, Leventhal, Crosnoe, and Dion (2010) concluded that the reading score discrepancy between low-income and wealthier students could be explained largely by the institutions to which they had access since birth. For example, poor and working class families rarely have access to high-quality early childhood education programs-the kind that support children's language (and other) learning in intensive, engaging ways (Kilburn & Karoly, 2008;Temple, Reynolds, & Arteaga, 2010).…”
Section: Stereotype 4: Poor People Are Linguistically Deficientmentioning
confidence: 99%
“…The medical model implies that disabilities reside within individuals, whereas the social models situate disability within structures that operate within culturally constructed and often problematic assumptions of normalcy (e.g., Lambert, 2015; Lewis-McCoy, 2016). Using the medical model, sociodemographic studies control for academic achievement with the assumption that it is possible to determine a student’s (dis)ability through academic assessments and other “clinically relevant factors” (Shifrer, 2018, p. 387), such as poverty, that may be indicative of neurological or developmental differences (e.g., Beaujean & McGlaughlin, 2014; Scarborough & McCrae, 2010; Simos et al, 2005; Temple et al, 2010). This approach is in line with the idea that “deviation” is related to limited “biological function resulting from a physical, cognitive, or sensory impairment,” which distinguishes two states of being “normal and pathological” (Baglieri & Lalvani, 2020, p. 19).…”
Section: Defining Disabilitymentioning
confidence: 99%
“…The use of achievement data is a good place to start. For example, while students’ academic achievement tends to be constant over time (Wu et al, 2014), it is important to remember how both structural and agency-focused studies show that academic performance, socio-emotional well-being, discipline outcomes, and the influence of poverty—individual student characteristics commonly associated with predicting student ability—are malleable and can be influenced by effective school-based programs and other teacher and classroom practices, without the need for special education classification (Bardon et al, 2008; Decker et al, 2007; Lo & Cartledge, 2006; Muschkin et al, 2015; Temple et al, 2010). Moreover, as ecological models show, student ability may similarly be influenced by racial contexts (Benner & Crosnoe, 2011; Benner et al, 2008; Eitle & Eitle, 2004; Ong-Dean, 2006).…”
Section: Conclusion and New Directions For Researchmentioning
confidence: 99%
“…Another set of studies focused on the association between birthweight and outcomes related to school trajectory measured by grade repetition and educational attainment [13,[18][19][20]. However, some studies did not find significant relationships between low birthweight and school performance and school attainment [18,21].…”
Section: Introductionmentioning
confidence: 99%